Elevated Epithelial Insulin-like Growth Factor Expression Is a Risk Factor for Lung Cancer Development - Kim, Woo-Young (2009)
Insulin-like growth factor 1 receptor (IGF-1R) signaling has been implicated in several human neoplasms. However, the role of serum levels of insulin-like growth factors (IGFs) in lung cancer risk is controversial. We assessed the role of tissue-derived IGFs in lung carcinogenesis. We found that IGF-1 and IGF-2 levels in bronchial tissue specimens containing high-grade dysplasia were significantly higher than in those containing normal epithelium, hyperplasia, and squamous metaplasia. Derivatives of human bronchial epithelial cell lines with activation mutation in KRAS (V12) or loss of p53 overexpressed IGF-1 and IGF-2. Transformed characteristics of these cells were significantly suppressed by inactivation of IGF-1R or inhibition of IGF-1 or IGF-2 expression but enhanced by ovrexpresion of insulin-like growth factor receptor (IGF-1R) or exposure to the tobacco carcinogens (TC) 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) and benzo[a]pyrene (BaP). We further determined the role of IGF-1R signaling in lung tumorigenesis by determining antitumor activities of the selective IGF-1R tyrosine kinase inhibitor cis-3-[3-(4-methyl-piperazin-l-yl)-cyclobutyl] -1-(2-phenyl-quinolin-7-yl) –imidazo [1,5-a]pyrazin-8-ylamine (PQIP) using an in vitro progressive cell system and an in vivo mouse model with a lung-specific IGF-1 transgene after exposure to TCs, including NNK plus BaP. Our results demonstrate that airway epithelial cells produce IGFs in an autocrine or paracrine manner, and these IGFs act jointly with TCs to enhance lung carcinogenesis. Further, the use of selective IGF-1R inhibitors may be a rational approach to controlling lung cancer.